Air temperature impacts on the non-variceal upper gastrointestinal bleeding - Oral, Ali Çağrı; Yalnız, Mehmet; Gözel, Nevzat; Özercan, Mübin; Bahçecioğlu, İbrahim Halil (Mümin POLAT, 2025)
ABSTRACT Objective: Our aim was to examine the correlation between daily weather temperature and the incidence of non-variceal upper gastrointestinal bleeding in patients admitted to the Gastroenterology department at Firat University Hospital Materials and Methods: The study was a retrospective analysis that involved collecting data from the electronic medical records of 56 patients at the Gastroenterology Department of Firat University Hospital. These patients were admitted with symptoms of hematemesis and/or melena. The study specifically focused on cases of non-variceal upper gastrointestinal bleeding (gastric or duodenal ulcers) that were diagnosed by upper gastrointestinal endoscopy between 2022 and 2023. Results: The study involved 56 patients, out of which 39 (69.6%) were male and 17 (30.4%) were female. All patients had symptoms of melena, and 24 (42.8%) also experienced hematemesis. 51.8% of the patients were using nonsteroidal anti-inflammatory drugs (NSAIDs), while 32.7% were taking antiplatelets and anticoagulants. It was noted that 25 (44.6%) of the cases occurred on days with an air temperature below 18°C, while 31 (55.4%) occurred on days with an air temperature above 18°C. Regarding age, 39 (69.6%) of the patients were over 60 years old. Despite significant bleeding from the ulcer based on the Forrest classification in this age group, patients under 60 years of age had longer hospitalization periods in both the inpatient ward and intensive care unit. Additionally, patients under 60 years had a higher risk of requiring esophageal stent (ES) replacement in this age group. Conclusion: Non-variceal upper gastrointestinal bleeding is a serious condition with high mortality and morbidity rates. There is a lack of sufficient data in the literature regarding the relationship between UGIB and air temperature, and more studies are needed
Keywords: ?Internal Diseases Nursing?; Dahili Hastalıklar Hemşireliği